Foreign MNC R&D Centers in India: A Study of their Publications, 2003-12 - Gupta, Ritu; Gupta, B.M. (DESIDOC Journal of Library & Information Technology, 2014)
The paper analysed 3040 publications of 21 most productive foreign multinational companies (MNCs) R&D centers in India during 2003-12, with a focus on the extent of their research output and citation impact, distribution of their publications by various subject fields, international collaborative publications, and national collaborating linkages with different type of Indian organisations. The data for the study has been derived from Scopus international multidisciplinary bibliographical database. The study found that the publications of these foreign R&D centers grew at an annual growth rate of 23.56 %, registered a citation impact of 2.29 and involved international collaboration in 46.02 % of its publications. The major areas of interest of these foreign R&D centers are computer science and engineering, followed by mathematics, materials science, physics, biochemistry, genetics & molecular biology, etc. The national collaborative linkages of foreign R&D centers are predominately with institutes of national importance. http://dx.doi.org/10.14429/djlit.34.5419